1998
DOI: 10.1007/s004250050415
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose-feeding leads to increased rates of nitrate assimilation, increased rates of α-oxoglutarate synthesis, and increased synthesis of a wide spectrum of amino acids in tobacco leaves

Abstract: To investigate the importance of the sugar supply for the regulation of nitrogen and organic acid metabolism, various sugars and nitrogenous compounds were supplied for 8 h to detached tobacco leaves in low light. (i) In control leaves supplied with water, there was a large decrease of the Nia transcript level, a 50% decline of nitrate reductase (NR) activity, starch increased and sugars remained low, nitrate decreased by 50%, and amino acids increased only slightly during the 8 h incubation. About half of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1
9

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 66 publications
7
122
1
9
Order By: Relevance
“…3b) and NIA activity (Fig. 3c, see also Morcuende et al 1998), compared to leaves that were supplied with water. When malate was supplied there was a 2-to 2·5-fold increase of malate in the leaves (Fig.…”
Section: Effect Of Supplying Organic Acids To Detached Leaves In the mentioning
confidence: 97%
“…3b) and NIA activity (Fig. 3c, see also Morcuende et al 1998), compared to leaves that were supplied with water. When malate was supplied there was a 2-to 2·5-fold increase of malate in the leaves (Fig.…”
Section: Effect Of Supplying Organic Acids To Detached Leaves In the mentioning
confidence: 97%
“…It is known that addition of ammonium leads to a rapid decrease of NR activity. This may be partly due to repression of Nia transcription by glutamine (Hoff et al 1994), and partly to increased post-translational inactivation and degradation of NR when glutamine is high (Scheible et al 1997c;Morcuende et al 1998). Despite these marked short-term effects of ammonium on nitrate assimilation, plants growing in ambient [CO 2 ] had similar NR activity on ammonium nitrate and on nitrate (see Fig.…”
Section: Elevated [Co 2 ] Alters the Nitrogen Status Dramatically Whementioning
confidence: 99%
“…In Plantago major, elevated [CO 2 ] led to a transient increase in NR activity, that was reversed after a few days (Fonseca, Bowsher & Stulen 1997). These reports of a decrease of NR activity in elevated [CO 2 ] are rather surprising, because exogenous sugars lead to increased expression of Nia (Cheng et al 1992;Vincentz et al 1993;Krapp et al 1993;Krapp & Stitt 1995;Morcuende et al 1998) and post-translational activation of NR (Kaiser & Huber 1994; Huber, Bachman & Huber 1996) in detached leaves. Recently Geiger et al (1998) showed that although elevated [CO 2 ] does not markedly increase the maximum NR activity in tobacco the diurnal regulation of NR is modified, allowing higher activity in the later part of the light period and during the night.…”
Section: Introductionmentioning
confidence: 99%
“…The high ammonium contents of young leaves are probably a result of strong photosynthetic nitrate reduction activity and photorespiration. In addition, young leaves have low contents in soluble carbohydrates, and sugar availability is known to be a limiting factor for ammonium assimilation (Morcuende et al, 1998). The high ammonium contents of senescent leaves are mainly due to protein degradation, amino acid deamination and nucleic acid catabolism, but also to photorespiration.…”
Section: Carbon and Nitrogen Metabolites As Regulators Of Leaf Senescmentioning
confidence: 99%